Equating of grades at basic and higher level of mathematics achievement - Hauptman, Alenka (Metodološki zvezki, 2010)
In Slovene General Matura, Mathematics is one of the compulsory subjects and it can be taken either at Basic or Higher Level of Achievement. Basic Level of Achievement is expressed by the classic five-grade scale from 1 to 5. Candidates at Higher Level of Achievement can get grades on scale from 1 to 8. Conversion of points into grades (i.e. getting points on tests and points at internal examination and then calculating those grades from the sum of points) on each Level is set independently, and we tried to find out if the same grade on each Level of Achievement corresponds to the same knowledge. Once grades are assigned they are used comparatively in selection procedures for admission to University. Both Basic and Higher Level in Mathematics include the same Part 1 of the exam. The second part of the exam (Part 2) is applied only to the Higher Level's candidates. Part 1 amounts to 80 % of the total points at Basic Level, and 53.3 % of total points at Higher Level. Higher Level's candidates get other 26.7 % of points in Part 2. Oral part of the exam represents 20 % of the grades at both Levels. In this paper we show discrepancy between knowledge within the same grades for candidates at Basic and Higher Level of Achievement on an example of a Mathematics exam from General Matura 2008. Rasch model within Item Response Theory framework was used to place item difficulties on common scale and the comparability of grade conversion on both Basic and Higher Level of Achievement was explored. The results show interesting differences in knowledge of candidates with the same grade at Basic and Higher Level of Achievement.
Keywords: Leaving examination; Matura; Matematika; Mathematics; Statistical analysis; Statistična analiza; Slovenia; Slovenija; težavnostne stopnje